A Framework for Business Model Design - Porrandokht Niroomand; Mahbobeh Ranjbar; Seyed Mohamad Aeraby; Behnaz Hajisadeghi (Journal of Information Technology Management)
This research was performed to recognize the ways ofBusiness Model Designing and explaining about the use of BusinessModel in technology-oriented firms and enterprises, and leads them towands the implementation of the plans and new ideas in order to enter tolabor market or maintenance of their situation in internal and globalmarkets. The essay was considering the concept of Business Model andthe relationship with Business strategies. Then various frameworks andmethods of business model including Faber business model framework,Mapit, Idea, Visitor and dynamic framework have been analyzed. Finallywhile introducing a recommended model for designing a business model;business model functions have investigated in conceptual framework. Thecurrent research has benefited from Meta-Synthesis method forqualitative analysis of investigations. The results show that the elements:organization, technology, financial resources, services/products, market,customers and phases: identification, designing, assessment andaggregation in business model designing have high importance.Examination of relation between importance, elements and businessmodel designing phases has shown that there is a positive and significantrelation between two structures. Based on data of this research, theaverage comparison one group test has supported business modelDesigning elements for developing technology based business.